ZERO-TRUST SECURITY IN CLOUD API INTEGRATIONS FOR HEALTHCARE SYSTEMS - VASA, RAJESH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The rapid growth of cloud-based integration platforms in healthcare has revolutionized electronic health record systems, telehealth services, and cross-institutional data sharing mechanisms fundamentally. Application Programming Interfaces have become decisive bridges for the flow of sensitive patient data between various stakeholders, significantly broadening the attack surface and placing healthcare organizations squarely in the crosshairs of advanced cyber actors. Conventional perimeter-centric models of security have been catastrophically insufficient in cloud-native environments, as they don't respond to insider threats, credential compromise, and API vulnerabilities that allow unauthorized entry into protected health information. This article introduces a thorough Zero-Trust security framework particularly tailored for healthcare cloud API integrations with continuous authentication, fine-grained attribute-based access controls, blockchain-enabled immutable audit trails, and real-time anomaly detection. The architecture combines industry-leading Identity and Access Management offerings with codified Zero-Trust principles in NIST Special Publication, utilizing new-generation API gateways, OAuth and OpenID Connect protocols, JSON Web Tokens for safe claims transfer, and TLS-encrypted communications. Experimental verification by wide-scale simulation of multi-organizational healthcare environments shows significant security enhancements, including extreme breach probability reduction, improved detection, and negligible effects on clinical workflows. The conclusions establish the importance of Zero-Trust architectures in safeguarding national healthcare infrastructure while facilitating safe, real-time data exchange necessary to facilitate coordinated patient care.